Результаты изучение особенностей поверхностной структуры стоматологических полимеров для съемного протезирования методом сканирующей микроскопии после их обработки разными полировочными пастами - Макєєв, Валентин Федорович; Скальський, Валентин Романович; Гуньовський, Ярослав Романович; Гуньовська, Романа Петрівна (Actual Dentistry, 2020)
Relevance. The article shows that the quality of the surface treatment of removable dentures, to a great extent, eliminates possible complications, contributes to the functional stability of orthopedic structures. The goal of the study:to research and carry out a comparative evaluation of the microstructure and micro relief of the surface of polymeric bases materials for removable dentures by scanning electron microscopy, depending on the materials used for polishing them. Materials and methods. The following samples of selected polymeric materials were prepared for the experiments: Ftoraks, Villacryl H Plus, and Vertex™ ThermoSens. Vertex™ ThermoGloss and Blue Shine polishing pastes were selected to evaluate the polishing properties. Electron microscopic examination of the materials was performed using a scanning electron microscope. Results: electron microscopic studies have shown that after the final surface burnishing of the samples with different polishing pastes, we observe that regardless of the selected paste, the surface quality is significantly improved. Of all polymers, the best quality has the surface after polishing with the ThermoGloss paste, and the surface of Villacryl H Plus specimens can be considered as perfectly processed in the studies performed. Conclusions. to the results of the performed researches, it is possible to conclude that the processing of the acrylic-free elastic bases polymers is rather complicated compared to the acrylic analogs. Key words: removable dentures, elastic polymers, acrylic polymers, scanning microscopy.